O trabalho artístico sócio-educativo de Ivaldo Bertazzo: projeto dança comunidade - Camargo, Daisy (2012)
This work is a study about Projeto Dança Comunidade (Community Dance Project) made from 2003 to 2007 by Ivaldo Bertazzo, an educator/dancer in a partnership with the Commerce Social Service of São Paulo SESC/SP. It was an educational Project for low-income adolescents living in São Paulo suburn who have been chosen by seven non-governmental organizations, by which those boys and girls have accomplished the Art learning in general and especially in dance. The aim of the Project was to reach personal autonomy and identity development of those adolescents by dance learning, broaden their sociocultural horizons as well as preparing them to carry out citizenship and for cultural resistance to globalized media. The author has made a theoretical research about critical theories concern to logocentric conception of education, whose result is the disdain of the body, and has present some authors who rely on the importance of corporeity in the learning process. Bertazzo s teaching/learning used in Community Dance Project aligns with these authors either. An empirical research by way of interviews was made with youngsters that took part in the Project and the analysis of this matter, based on the Edgar Morin s complex thinking, presents Bertazzo s pedagogy as it has been experienced by the students and how possible it turned to be so that the Project achieved its purposes.